5 MeV Proton irradiation effects on 200 GHz silicon–germanium heterojunction bipolar transistors. Issue 11 (2nd December 2017) - Gnana Prakash, A. P.; Hegde, Vinayakprasanna N.; Pradeep, T. M.; Pushpa, N.; Bajpai, P. K.; Patel, S. P.; Trivedi, Tarkeshwar; Cressler, J. D.
ABSTRACT: The total dose effects of 5 MeV proton and Co-60 gamma irradiation in the dose range from 1 to 100 Mrad on advanced 200 GHz Silicon–Germanium heterojunction bipolar transistors (SiGe HBTs) are investigated. The SRIM simulation study was conducted to understand the energy loss of 5 MeV proton ions in SiGe HBT structure. Pre- and post-radiation DC figure of merits such as forward- and inverse-mode Gummel characteristics, excess base current, DC current gain and output characteristics were used to quantify the radiation tolerance of the devices. The results show that the proton creates a significant amount of damages in the surface and bulk of the transistor when compared with gamma irradiation. The SiGe HBTs shows robust ionizing radiation tolerance even up to a total dose of 100 Mrad for both radiations.